Sports activity limitation during the COVID-19 pandemic in young Italian athletes: impact on mental health in children, adolescents, and young adults - Tomezzoli, Elisa; D'Ecclesiis, Oriana; Raimondi, Sara; Pravettoni, Gabriella; Cammarata, Giulio; Testa, Giovanna; Bellerba, Federica; Gnagnarella, Patrizia; Iannuzzo, Maria Luisa; Sartorio, Alessandro; Sasso, Clementina; Ricci, Dorotea; et al. (Frontiers in Public Health, 2023)
Introduction: The closure of sports centres was implemented as a preventive measure to mitigate the transmission of SARS-CoV-2. Given the observed global decline in physical activity and con-current rise in sedentary behaviour, even among younger age groups, a retrospective cross-sectional study was undertaken to evaluate the effects of this measure on menta health in children, adolescents, and young adults during the initial phases of the COVID-19 pandemic. Methods: A total of 1,717 non-professional athletes (age range: 6-25; 53.9% males, 44.6% fe-males) completed an online questionnaire including widely used and validated measures for men-tal health assessment (SDQ and PGWB-S) and questions regarding sociodemographic characteris-tics (such as gender), physical activity, and screen time. The association between mental health and sociodemographic characteristics, physical activity, and screen time was evaluated by using univariate and multivariable logistic regression models. Results: In children and adolescents, the incidence of psychological difficulties was associated with not being physically active (OR=1.49;95%CI:1.09,2.07;p=0.015). Engaging in physical activ-ity during the period of closures, particularly if more than twice a week, was significantly associat-ed with less psychological difficulties for children/adolescents (OR=0.54;95%CI:0.35,0.82;p=0.004) and psychological symptoms (i.e., psychological well-being lower than the median) for youth/young adults (OR=0.25;95%CI:0.14,0.45;p<0.001). More psy-chological difficulties were also found in males for children and adolescents (OR=1.37;95%CI:1.06,1.79;p=0.018). However, young adult males showed less psychological symptoms than females (OR=0.35;95%CI:0.22,0.55;p=0.001). Additionally, a greater amount of screen time was associated with a higher incidence of psychological symptoms in the whole sam-ple. Conclusions: Our results confirm the positive impact of physical activity on mental health during the COVID-19 pandemic among younger age groups. They also provide valuable insights into the risk-benefit relationship of interrupting sports activities as a preventive measure for infectious dis-eases.